Settlement Policy of Resettling Country (History and Modernity). (A.V. Krilov. Israeli Settlements on the Arab Occupied Territories (1967-2007). M. 2011 - A. V. Fedorchenko (Vestnik MGIMO-Universiteta, 2011)
.